(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2005)
The present paper is the first in a series devoted to the revision of the Pliocene naticids of Northern and Central Italy. It recovers some previously disregarded but valid species and expands the number of naticine taxa (Tectonatica excluded) from four to twelve. Of these, one belongs to the genus Natica Scopoli, 1777, the others are assigned to the genus Cochlis Röding, 1798 which is reused herein for the first time after more than one century. The vast material examined (personal and museum collections) has allowed to analyze all shell and opercular characters, in terms of range of variation and significance in species recognition. The study demonstrates that the morphological characters of the teleoconch, such as the height of the spire, the suture, the umbilical features and the sculpture (subsutural axial wrinkles), are diagnostic only in some instances as it happens with the color. The operculum stands as the most significant diagnostic element in that is species-specific and, thence, sufficient to recognize each taxon. The protoconch is relevant as well to distinguish several, but not all species. The characters which are necessary and/or sufficient for the identification of the species considered in this study are summarized in the conclusive remarks. All the twelve taxa considered in this study are described and commented in the systematic account. One species, Cochlis sulcogradata, and one subspecies, Cochlis raropunctata obliquicallosa, are proposed as new.